2016
DOI: 10.18632/oncotarget.12720
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes goat spermatogonia stem cells (SSCs) proliferation by stimulating glial cell line-derived neurotrophic factor (GDNF) production in Sertoli cells

Abstract: Melatonin has been reported to be an important endogenous hormone for regulating neurogenesis, immunityand the biological clock. Recently, the effects of melatonin on neural stem cells (NSCs), mesenchymal stem cells(MSCs), and induced pluripotent stem cells(iPSCs) have been reported; however, the effects of melatonin on spermatogonia stem cells (SSCs) are not clear. Here, 1μM and 1nM melatonin was added to medium when goat SSCs were cultured in vitro, the results showed that melatonin could increase the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…In a previous study, we demonstrated for the first time that melatonin activated Akt phosphorylation following FCI in mice [14], which was later shown in various tissues, including brain [4], [5], [15], seminiferous tubules [31] as well as in cancer cells [32]. Melatonin-induced apoptosis of cancer cells is intervened by Pi3K/Akt pathway [32].…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study, we demonstrated for the first time that melatonin activated Akt phosphorylation following FCI in mice [14], which was later shown in various tissues, including brain [4], [5], [15], seminiferous tubules [31] as well as in cancer cells [32]. Melatonin-induced apoptosis of cancer cells is intervened by Pi3K/Akt pathway [32].…”
Section: Discussionmentioning
confidence: 86%
“…A couple of studies revealed that melatonin alleviates Cd-induced cellular stress and germ cell apoptosis in testes [50] and prevents bisphenol A-induced apoptosis by controlling BCL2 expression and ameliorating oxidative stress in the testes and sperm [51]. Furthermore, melatonin had a positive influence on the efficiency of male germ cell differentiation [52], and it can promote goat SSC proliferation by stimulating GDNF production in Sertoli cells [53]. …”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been shown to be involved in male reproduction by modulating steroid hormone secretion 16 as well as by being involved in the proliferation of spermatogenic cells. 17 Moreover, melatonin protects the testis against hyperthermia, environmental toxins, and drug-induced damage [18][19][20] due to its lipophilic and hydrophilic free radical scavenging characteristics. 21 Indeed, previous studies have demonstrated the beneficial effects of melatonin treatment on testicular cells under pathological conditions; however, it is unclear whether melatonin can prevent obesity-associated male infertility, specifically in PAinduced testicular damage.…”
Section: Introductionmentioning
confidence: 99%